Probabilitas Perusahaan Manufaktur yang Tercatat di Bursa Efek Indonesia dalam Membayar Dividen - Setiawan, Rahmat; Harmasanto, Denny Hardiko (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2019)
This study aims to examine the factors that influence the probability of manufacturing companies in dividends payout policy. Variables including profitability, leverage, working capital, cash reserves, cash flow, tangible assets, size and age of the company and GDP growth are considered as determinants in the company's dividend policy. Samples were taken from 112 manufacturing companies listed on the Indonesia Stock Exchange during the 2012-2018 period. Panel data analysis uses the company's annual financial statements which were tested using logistic regression. The results of the study found the fact that profitability, cash reserves, operating cash flow and firm size had a positive and significant effect on the probability of a company paying dividends. Conversely, leverage, net working capital, tangible assets and the age of the company have a negative and significant effect.